The Influence of Complex Instruction Type Cooperative Learning Models on Student History Learning Outcomes SMA Negeri 5 Banda Aceh - Riska Maizura (Universitas Syiah Kuala, 2022)
This article aims to know the effect of the cooperative learning model of complex instruction type on history learning outcomes of class XI IPS students SMA Negeri 5 Banda Aceh. The method used in this research is quasi-experimental with the form of design used being the nonequivalent control group. The population in this study are all students of class XI IPS SMA Negeri 5 Banda Aceh. The sample in this study was XI IPS 1 as an experimental class and XI IPS 2 as a control class, samples were taken by purposive sampling technique. Data collection techniques used are test and documentation. Data analysis techniques using SPSS version 20. The results showed that the cooperative learning model of complex instruction type influences student history learning outcome with an average student learning outcomes of students in class XI IPS 1 is 73,45 while class XI IPS 2 is 58,50. The results of data processing using Mann-Whithney test on the experimental class and control class showed that Asymp. Sig. (2-tailed) that is 0,001 less than 0,05, so is accepted and is rejected, it means that there is an effect of the model on history learning outcomes of class XI IPS students.